A City for People in the Light of Studies on Urban Stress: Case Study of a Medium-sized City in Poland - Zduńska Wola - Rzeńca, Agnieszka; Wierucka , Oliwia (Studia Ecologiae et Bioethicae, 2022)
Alarming data revealing the poor quality of the urban environment as well as international documents calling for urban policies to be re-orientated towards more sustainable growth (e.g., IPCC Sixth Assessment Report: Climate Change 2022) force greater integration and deepening of the existing urban studies, as well as promote the initiation of new research. This paper focuses on the perception of urban stress in contemporary cities and towns and on identifying factors that produce it. The case study features a deliberately selected town of Zduńska Wola, from the Łódź Voivodeship in Poland. The thesis proposed in this paper reads: Contemporary towns and cities, including Zduńska Wola, generate urban stress that is experienced by its residents. Significant aspects of this work deal with the specification of differences in the interpretation of urban stress factors. Based on the study of the literature on the issue of stress, it appears that among the most often listed stressors are the ones connected with the condition and quality of the environment, which was confirmed by opinions expressed by inhabitants of Zduńska Wola (more than 70% of respondents mentioned pollution as a stress factor). Interestingly, our questionnaire-based studies revealed that commuters to the city reported higher levels of perceived stress caused by neglected urban space, than permanent residents.